Keanekaragaman Serangga di Pertanaman Kopi pada Tiga Jenis Pohon Penaung - Susilawati Susilawati; Gusti Indriati; Mahardika Puspitasari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Susilawati S, Indriati G, Puspitasari M. 2020. The diversity of insects in coffee plantation on three types of shade trees. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The presence of insects in an agricultural habitat is affected by several factors, such as vegetation around agricultural land. The objectives of this research was to study the effect of different types of shade trees in coffee plantations on insect diversity. Research conducted at the Pakuwon Experimental Station and the Integrated Laboratory of Balittri in January-July 2019. Insects sampling was observe using yellow pan traps and pitfall traps on the field. In each coffee plantation, 15 yellow pan traps (YPT) and pitfall traps (PT) were installed for 24 hour. Three types of shade trees found in this research were (1) Philippine Tung (Reutealis trisperma), (2) a combination Philippine Tung (Reutealis trisperma) with Gliricidia sepium, (3) a combination Banana (Musa sp.) with Gliricidia sepium. Insect identification was carried out morphologically from Order to morphospecies. Diversity, number of species and abundance were analyzed using the R statistic. The results showed that there were seven orders of insects found in the coffee plant, namely Hymenoptera, Diptera, Orthoptera, Hemiptera, Coleoptera, and Dermaptera. The explored dominant insects were from the order Hymenoptera of the Formicidae, namely Anoplolepis sp. Tetramorium sp., Odontoponera sp., and the Orthoptera family Gryllidae, namely Gryllus sp. The statistical analysis result showed that differences in shade trees affected the diversity and abundance of insects.